Trouble Showed the Way : Women, Men, and Trade in the Nairobi Area, 1890 - 1990 - Robertson, Claire C., 1944- (Book collections on Project MUSE., 1997)
Award-winner Claire Robertson employs a variety of approaches to analyze and weave together this wide-ranging study. Her book provides an extensive case study of historical transformations in gender, agriculture, residence, and civil society. Based on archival documents, library sources (fiction and nonfiction, primary and secondary), surveys and oral histories, participant observation, and quantitative and qualitative analysis, Robertson breaks new ground by focusing on traders in one commodity, dried staples, and comparing and contrasting the evolution of women's trade with men's trade.